Artificial Intelligence in Brazilian Judicial Branch - da Silva DANTAS, Frederico Widson da Silva DANTAS; Graciéla Farias BRAZ (Revista Jurídica Portucalense, 2022)
The Brazilian Judicial Branch has been experiencing the effects of the digital transformation, following the enlarged use of information technology, phenomenon that tends to be improved by investments made in new automation tools and development of artificial intelligence systems, to assist judicial decision-making. In Brazil, the ongoing debate over the risks and benefits of artificial intelligence is current, with three different bills introduced in Congress, meanwhile, the National Justice Counsel (CNJ) has issued a regulation adopting the European Ethical Charter on the use of artificial intelligence artificial intelligence in judicial systems and their environment. While the artificial intelligence legal framework is still being debated in Congress, there are no obstacles for the use of artificial intelligence systems in judicial decision-making, especially since the Brazilian Judiciary employs the artificial intelligence technology as a management tool to rationalize the treatment of repetitive demands, in which there is no fact review and the adversarial principal is mitigated, taking into account reasons pertinent to legal certainty and isonomy, solution compatible with the cooperation model, brought in by the 2015 Code of Civil Procedure.